Teachers’ Perceptions Toward Video as a Tool for Feedback on Students’ Oral Performance - Park, Jaeuk (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2023)
Video technology has the potential to improve opportunities for students to benefit from feedback that is essential for learning. However, previous studies have all dealt with videos of tutors, rather than videos of students’ performances. This study explores whether video technology contributes to the quality of feedback on students’ oral language performance and investigates how language teachers perceive contemporary technology regarding student education. Participants in the study were eight incumbent teachers involved in language education. The interview data suggested that the teachers seemed to be very positive about using video technology as a tool for feedback. The technology not only allowed for evidence-based accounts which served to enrich the quality of feedback, but also enabled them to highlight specific aspects of oral performances and create feedback that is conducive to understanding. The findings of this study showed that technology-enhanced evidence-based feedback will be able to provide an important supplement to written feedback, adding one more mode for an effective feedback process.